2014
DOI: 10.1097/coc.0b013e31827de92b
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Poliglumex, Temozolomide, and Radiation for Newly Diagnosed High-grade Glioma

Abstract: PPX could not be safely combined with temozolomide due to grade 4 hematologic toxicity. However, the favorable progression-free and overall survival suggest that PPX may enhance radiation for glioblastoma. A randomized study of single agent PPX/radiation versus temozolomide/radiation for glioblastoma without MGMT methylation is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Instead, they contained CD68-positive cells, suggesting a contribution from macrophages and/or activated microglia, and "quiescent" tumor cells with Ki-67 (cellular marker for proliferation) typically <5%. 18 Thus, the composition of PsP in our study appears to reside somewhere between necrosis and active tumor in a histopathologic spectrum, likely contributing to the overlapping rCBVs for PsP and PD at initial progressive enhancement. .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Instead, they contained CD68-positive cells, suggesting a contribution from macrophages and/or activated microglia, and "quiescent" tumor cells with Ki-67 (cellular marker for proliferation) typically <5%. 18 Thus, the composition of PsP in our study appears to reside somewhere between necrosis and active tumor in a histopathologic spectrum, likely contributing to the overlapping rCBVs for PsP and PD at initial progressive enhancement. .…”
Section: Discussionmentioning
confidence: 95%
“…18 Institutional Review Boards of participating hospitals approved this HIPAA-compliant study. Patients received PPX (40 to 50 mg/m 2 ), TMZ (75 mg/m 2 /d), and concurrent radiotherapy (2 Gy/d, 5 d/wk, 60 Gy total dose) over 6 weeks, and adjuvant TMZ (150 to 200 mg/m 2 Â5 d every 28 d) until disease progression.…”
Section: Patients and Clinical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The commonly accepted treatment protocol for GBM involves surgical resection, followed by chemotherapy treatment (usually with TMZ as adjuvant chemotherapy), and radiation [6], but a recent study has demonstrated the effectiveness of combination therapies using TMZ and paclitaxel [64]. Another study, using paclitaxel poliglumex in combination with TMZ and concurrent radiation, showed some promise in terms of overall survival, but the drugs could not be combined safely due to toxicity issues [65]. Therefore, it would be useful to measure the effectiveness of SYMPK knockdown to enhance the effectiveness of a combined chemotherapeutic regimen in GSCs.…”
Section: Potential Role Of Sympk In Gliomamentioning
confidence: 96%